Severe Spasm of the Renal Artery after Blunt Abdominal Trauma Simulating End-Organ Infarction - Adem Ucar; Aghakishi Yahyayev; Ayaz Agayev; Fatih Yanar; Selim Bakan; Mesut Bulakci; Tolga Akman; Ensar Yekeler (Case Reports in Medicine)
Traumatic occlusion of the renal artery is a serious injury. Management differs according to the grade of injury. In most circumstances, emergency surgical revascularization or endovascular intervention is required. We describe the case of a child with multiorgan injuries and spasm of the main renal artery after blunt trauma simulating arterial occlusion or end-organ infarction.